2023
DOI: 10.1007/s10694-023-01387-7
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Flame-Retardant Flax Fabrics by Engineered Layer-by-Layer Surface Functionalization with Phytic Acid and Polyethylenimine

Abstract: New generation of mission-oriented fabrics meets advanced requirements; such as electrical conductivity, flame retardancy, and anti-bacterial properties. However, sustainability concerns still are on-demand in fabrication of multi-functional fabrics. In this work, we used a bio-based phosphorus molecule (phytic acid, PA) to reinforce flax fabrics against flame via layer-by-layer consecutive surface modification. First, the flax fabric was treated with PA. Then, polyethylenimine (PEI) was localized above it to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The treated fabrics displayed an effective flame retardancy with 41% reduction in the peak heat rate release (pHRR). Ehsanimehr et al 25 also used PA to modify flax fabrics via the same method. The authors showed that values of pHRR of treated fabrics significantly decreased by about 77%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treated fabrics displayed an effective flame retardancy with 41% reduction in the peak heat rate release (pHRR). Ehsanimehr et al 25 also used PA to modify flax fabrics via the same method. The authors showed that values of pHRR of treated fabrics significantly decreased by about 77%.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on environmentally friendly flame retardants, especially biobased ones . PA, which is a natural source of phosphorus, was highly investigated as a flame-retardant biomolecule. , …”
Section: Introductionmentioning
confidence: 99%